Waste Management for the Covid-19 Essentials Kit: What Role Does Government Perform? - Dewi Sekar Kencono (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2023)
This paper aims to study the environmental impact of Covid-19 Essentials Kit’s Waste, such as one time use face mask, and hand 1most importantly in the economic sector. Yet, even beyond matters of health and the economy, the impact of the Covid-19 virus is significant to the environmental sector. One time face mask and hand sanitizers have been continuously being use by the citizens as it is compulsory by the government and has been become an essentials kit and almost every people has it with them. Further than that, contaminated protective equipment that being use by the common person might not have been disposed properly. Proper disposal is need to reduce the contamination made by those essentials kit to the soil, water, and air. Government cooperation with other concerned parties is essential to the creation of mutual security and comfort for the surrounding environment. In conclusion, the government can promote various programs, such as making the public aware of the importance of discarding their masks in the trash and utilizing what is left in the recycling process.